Formulation And Evaluation Of Telang Flower (Clitoria Ternatea L.) Extract Gel Preparation With Tragacanth As Gelling Agent And Antioxidant Activity Test - Nurwaini, Setyo; Amanda, Alifah Tasya (Pharmacon: Jurnal Farmasi Indonesia, 2024)
Telang flower has antioxidant activity as a scavenger of free radicals. Formulation in gel form can facilitate its use as a cosmetic preparation. This study aims to determine the characteristics of telang flower extract gel at different concentrations of tragacanth as a gelling agent and its antioxidant activity.Gel formula of telang flower extract with different concentration levels of tragacanth, namely 3%, 4%, and 5%. Gel evaluation includes organoleptic test, homogeneity, pH, spreadability, stickiness, and viscosity. The best formula will be tested for antioxidant activity.Based on the gel characteristics of telang flower extract, F3 has good physical properties, namely pH value of 7.28 ± 0.06, viscosity of 2133.3 ± 23.09 cP, spreadability of 6.05 ± 0.13 cm, and stickiness of 1.17 ± 0.07 seconds. The telang flower extract exhibited an IC50 value of 71.125 ppm, classifying it as strong antixodant. The IC50 value of telang flower extract gel was 92.867 ppm